Influences of environmental concerns and the scepticism in front of the advertising in the green products consumptiON - da Silva, Dirceu; Urdan, André Torres; Merlo, Edgard Monforte; Dias, Karina Tonelli Silveira [UNESP] (University Nove de Julho, 2015)
Doubts remain about whether and how (direct and/or indirect via) the individual converts Environmental Concern in the Purchase of Green Products, especially in the specifics of the Brazilian reality. The very Purchase Intention of these products can be not confirmed at the time of purchase. In this sphere, furthermore, a barrier can be on the influence of the Skepticism towards Advertising, unfavorably hitting goods and services that, on the market, are spread as ecologically superior; barrier little investigated so far. These are relevant issues under the scientific, social and managerial prisms, addressed in this article by a quantitative research, through a survey of 1233 persons, from three Brazilian capitals and supermarket buyers. It was evidenced that, in the sample, the Environmental Concern affects the Purchase Intention of Green Products, but not the Declared Purchase. In turn, the Skepticism Towards Advertising negatively influence the Declared Purchase, of Green Products, but do not Purchase Intention of them. At the end, some scientific and managerial implications are exposed, as wells as directions for future research.
Influências da preocupação ambiental e do ceticismo frente à propaganda no consumo de produtos verdes
Keywords: Advertising; Consumer; Declared Purchase; Environmental Concern; Green Products; Purchase Intention; Skepticism